197k views
5 votes
Simplify the expression (-2y+5)(y+3)

1 Answer

6 votes

Answer:


=-2y^2-y+15

Explanation:


\left(-2y+5\right)\left(y+3\right)\\\mathrm{Apply\:FOIL\:method}:\quad \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd\\a=-2y,\:b=5,\:c=y,\:d=3\\=\left(-2y\right)y+\left(-2y\right)\cdot \:3+5y+5\cdot \:3\\Apply\:minus-plus\:rules\\+\left(-a\right)=-a\\=-2yy-2\cdot \:3y+5y+5\cdot \:3\\\mathrm{Simplify}\:-2yy-2\cdot \:3y+5y+5\cdot \:3:\quad -2y^2-y+15\\-2yy-2\cdot \:3y+5y+5\cdot \:3


2yy=2y^2\\2yy\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)\\yy=\:y^(1+1)\\=2y^(1+1)\\\mathrm{Add\:the\:numbers:}\:1+1=2\\=2y^2\\2\cdot \:3y=6y\\2\cdot \:3y\\\mathrm{Multiply\:the\:numbers:}\:2\cdot \:3=6\\=6y


5\cdot \:3=15\\5\cdot \:3\\\mathrm{Multiply\:the\:numbers:}\:5\cdot \:3=15\\=15\\=-2y^2-6y+5y+15\\\mathrm{Add\:similar\:elements:}\:-6y+5y=-y\\=-2y^2-y+15

User Itang Sanjana
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.